The pomelo peel and derived nanoscale-precision gradient silica foams. Issue 2 (1st April 2012) - Paris, Oskar; Zollfrank, Cordt; Thielen, Marc; Seidel, Robin; Van Opdenbosch, Daniel; Fey, Tobias; Fritz-Popovski, Gerhard; Speck, Thomas
Abstract : In this work, the three-dimensional (3D) structure and replication of pomelo (Citrus maxima) peel as silica on several hierarchical levels is reported. The native peel as well as mineralized and calcined replica were assessed by their dimensional changes and their structures investigated by scanning electron microscopy. Computed x-ray microtomography yielded a detailed 3D model of the gradient foam structure, demonstrating the true replication of the entire structure on the millimeter and micrometer scales. SAXS evidenced the replication of the single cellulose fibrils on the nanometer scale. This work therefore demonstrates the possibility of transforming complex low-density polysaccharide templates into silica with nanometer precision, yielding inorganic, temperature-resistant gradient foam structures.